Coligand effects on the architectures and magnetic properties of octahedral cobalt(ii) complexes with easy-axis magnetic anisotropy. Issue 13 (13th March 2020) - Wu, Yuewei; Xi, Jing; Yang, Jinhui; Song, Weiming; Luo, Shuchang; Wang, Zheng; Liu, Xiangyu
Abstract : Coligand effects lead to two mononuclear octahedral Co(ii ) complexes exhibiting easy-axis magnetic anisotropies and distinct magnetic properties. Abstract : Two mononuclear azido–cobalt(ii ) complexes, with the formulas [Co(3, 3-Hbpt)2 (N3 )2 (H2 O)2 ] (1 ) and [Co(abpt)2 (N3 )2 ]·H2 O (2 ) (3, 3-Hbpt = 1 H -3, 5-bis(3-pyridyl)-1, 2, 4-triazole; abpt = 4-amino-3, 5-bis(2-pyridyl)-1, 2, 4-triazole), have been prepared by altering the pyridyl-triazole coligands. In both complexes, the Co(ii ) centers feature hexa-coordinated environments with distorted octahedra in which the axial sites are identical, whereas the equatorial environments are finely modulated by the distinct chemical nature of the different coligands. It is worth noting that the distinct intermetallic distances in the two complexes (10.302 Å for 1 and 6.576 Å for 2 ) unambiguously cause a disparity in intermolecular interactions, implying their dissimilar magnetic behaviours. As a result, alternating current dynamic susceptibility measurements show that only 2 exhibits field-induced slow relaxation of magnetization with an effective energy barrier of 11.29 K, though large easy-axis magnetic anisotropies for both complexes are unveiled by combined analyses of the magnetic data and ab initio calculations.